Cross-Cutting Affiliation in Regional Election in Indonesia - Anang Sujoko; Zidna Al Izzah; Dicky Wahyudi (Komunikator, 2022)
This paper aims to reveal how the political background colors the political communication process in winning Abu (Muhammadiyah) and Lilik (Muslimat Nahdatul Ulama) in the 2018 regional election in Kediri City. This research uses qualitative research methods with instrumental case study approach, and we use data collection techniques in the form of in-depth interviews and documentation. The results show that the different political backgrounds of the candidates actually create cross-cutting affiliations between Muhammadiyah and NU Muslim society in Kediri City to provide support for Abu and Lilik in the Kediri City regional election. This cross-cutting affiliation is not created naturally, but is determined by ‘Wong Tebangan’ as King Maker. Political lobbying by a ‘Gus’ attracted support from several NU kyai in Kediri City. Then, holding regular NU Muslimat recitations and stall forums became a means of maintaining the integrity of support for attacks from other candidates. Finally, the research also revealed how Javanese beliefs, modern political instruments, and religion are used in winning elections.